Remote sensing materials for creating cards for agriculture - Курач, Тамара Миколаївна; Шемчук, М. (Київський національний університет імені Тараса Шевченка, 2017)
Досліджено особливості використання матеріалів дистанційного зондування при створенні карт для потреб сільського господарства. Отримано та опрацьовано матеріали аерофотознімання групи полів у Шепетівському районі Хмельницької області, з яких створено зразки наочних картографічних матеріалів. Використано методи візуального дешифрування та цифрового оброблення знімків шляхом обрахування вегетаційного індекса NDVI. Запропоновані технології дозволяють вчасно виявити аномалії на полях сільськогосподарських культур та вчасно реагувати на них, при умові постійного моніторингу полів протягом всього періоду вегетації сільськогосподарських культур. Розроблені матеріали моніторингу дозволили підняти прибуток підприємства та врожайність сільськогосподарських культур.

The peculiarities of using remote sensing materials in the development of maps for the needs of agriculture are explored. Aerial photographs of the group of fields in the Shepetovsky district of the Khmelnitsky region were obtained and processed, from which samples of visual cartographic materials were created. To ensure the monitoring of the necessary materials for aerial surveying, namely, four flights at two heights – 150 m, 800 m. Methods of visual decoding and digital image processing using the NDVI vegetation index are used. Non-synthesized snapshots reveal various weeds that visually differ from cultivated plants and determine their prevalence on the eye. The condition of the development of plants, the presence of sieve, and various anomalies have been estimated, that is, the weak points have been previously estimated, which should be paid attention in further research. Another important characteristic that can be determined by the vegetation index (its various values) is the isolation of various plant species. With regard to this, one can determine the boundaries of different crops, as well as determine the amount and intensity of weeds. At the same time it is possible to reveal the characteristics of the state of the plant itself, because in places where the value of the weed index prevails, the cultivated plant is clearly in a state of depression. When calculating and analyzing the results, one should carefully approach the definition of the correct index for plants in a normal state. Indeed, since for different plants it differs, different weeds can have as much or more than the reference value for a given plant. This should be taken into account when interpreting the result of the study. Another characteristic that follows from the value of the vegetative index is the density of the plants themselves. In many cases, intense color means a large mass of plants, with their normal state, allows you to get important information for farmers. Obtained infrared images need not be transformed using indices to obtain the necessary information. They exhibit moisture and humidified areas quite well, which is also important for farming. Moisturized areas negatively affect vegetation of plants. In addition, the wetted areas correlate well with the relief of the field. According to the results of the work, photoschemes with a resolution of 15-25 cm and individual fragments of fields with a resolution of 1.5 – 3 cm were made. The proposed technologies allow detecting anomalies in fields of agricultural crops in a timely manner and responding in a timely manner to them, provided that the fields are monitored continuously throughout the period of vegetation of crops. The developed monitoring materials made it possible to increase the company’s profits and yields of agricultural crops.
Матеріали дистанційного зондування при створенні карт для сільського господарства
Жлобак Г.М. Використання методів дистанційного зондування Землі для моніторингу агроресурсів України / Г.М. Жлобак // Космічна наука і технологія. – 2010. – Т. 16. № 6. – С. 16–23. Зацерковний В. І. Використання ГІС та ДЗЗ для моніторингу сільськогосподарських земель / В. І. Зацерковний, С. В. Кривоберець, В. В. Сергієнко // Чернігівський науковий часопис. Серія 2, Техніка і природа. – 2011. – №2(2). – С. 40-48. Інститут агроекології і природокористування НААНУ [Електронний ресурс]. – Режим доступу: http://agroeco.at.ua/. Інститут фізіології рослин і генетики НАН України [Електронний ресурс]. – Режим доступу: http://www.ifrg.kiev.ua/. Cessna. Textron Aviation [Електронний ресурс]. – Режим доступу: http://cessna.txtav.com/. IGI Systems [Електронний ресурс]. – Режим доступу: http://www.igi-systems.com/home.html.
Keywords: матеріали аерофотознімання; матеріали дистанційного зондування; дешифрування; вегетаційний індекс NDVI; aerial photography materials; remote sensing materials; decoding; vegetation index NDVI